Nationwide assessment of fall risk and protective factors among older adults in Saudi Arabia - Ahmad A. Alharbi; Abdulaziz A. Albalwi; Hamad S. Al Amer; Samia A. Alamrani; Hani F. Albalawi; Fawaz D. Alrashedi; Majed Y. Muthaffar; Mousa A. Albalwi; Yousef M. Alshehre; Hadeel R. Bakhsh; Maysoun N. Saleh (PLoS ONE, 2025)
In Saudi Arabia, nearly half of older adults (49.9%) experience at least one fall annually. Despite its global and regional significance, research on fall risk factors in Saudi Arabia remains limited, with most studies concentrating on specific cities or subpopulations. This study investigated factors associated with falls among older adults across Saudi Arabia. In this cross-sectional study, 473 (58.8% female) older adults (58.4% aged 65–69 years) completed a questionnaire, where we collected data on demographic and health characteristics; additionally, participants completed the Arabic version of the Fall Risk Questionnaire (FRQ-AV). Both descriptive and inferential statistical methods, including logistic regression, were used to analyze the data using SPSS. Based on the FRQ-AV, 168 (35.5%) participants were identified as at risk of falling. After multivariable adjustment, the following significant risk factors were identified: age 70–74 (adjusted odds ratio [aOR]=2.52; 95% confidence interval [CI]: 1.35–4.68; p = 0.004) and ≥80 (aOR=4.85; 95% CI: 1.50–15.63; p = 0.008) years; coexisting diabetes and hypertension (aOR=3.59; 95% CI: 1.75–7.35; p < 0.0005); being somewhat (aOR=4.64; 95% CI: 1.78–12.12; p = 0.002), fairly (aOR=11.36; 95% CI: 4.04–31.91; p < 0.0005), or very afraid of falling (aOR=32.81; 95% CI: 10.88–98.99; p < 0.0005); and falling 1–2 (aOR=5.27; 95% CI: 2.80–9.89; p < 0.0005), 3–4 (aOR=13.06; 95% CI: 5.50–30.98; p < 0.0005), or five (aOR = 12.23; 95% CI: 2.88–51.83; p = 0.001) times in the past year. Protective factors included university education (OR=0.39; 95% CI: 0.22–0.68; p = 0.001) and engagement in physical activity (aOR=0.46; 95% CI: 0.26–0.81; p = 0.007). This study offers significant insights into fall factors and preventive strategies among older adults in Saudi Arabia. This study’s results can help in developing and implementing efficient fall prevention strategies nationwide.